Development of the Kyro Model as an Intervention Strategy in Literacy Improvement - Resti, Ulis; Yusuf Muslihin, Heri; Indihadi, Dian (Papanda Publisher, 2025)
Reading and writing are fundamental cognitive skills that significantly impact academic success and critical thinking development. In Indonesia, many students struggle with complex text comprehension due to ineffective instructional strategies and low reading motivation. This challenge necessitates the development of innovative instructional models that address diverse learning needs and promote student engagement in literacy activities. This study employed a systematic literature review approach to develop the KYRO model (Knowledge, Understanding, Responsibility, and Opportunity) for literacy improvement. The research process involved identifying research objectives, conducting comprehensive literature searches across academic databases, applying selection criteria for source quality and relevance, performing thematic analysis, and conceptualizing the model based on theoretical foundations including Vygotsky's sociocultural theory and culturally responsive teaching principles. The analysis revealed that the KYRO model integrates interactive and collaborative strategies grounded in sociocultural learning theory. The model emphasizes four core components: Skills (Keterampilan), Confidence (Yakin), Responsiveness (Responsif), and Optimal Learning (Optimal). Implementation of this model demonstrated potential for increasing student motivation, engagement in reading and writing activities, text analysis abilities, creativity in writing, and communication confidence. The model's flexibility accommodates various learning styles while promoting active participation and deeper textual understanding. The KYRO model offers a comprehensive framework that addresses cognitive, emotional, and social aspects of literacy learning. By incorporating peer collaboration, scaffolding within the Zone of Proximal Development, and technology integration, the model creates engaging learning environments responsive to student needs. Further empirical research is needed to validate the model's effectiveness across diverse educational contexts and inform curriculum development strategies.